Identifying Protective Drugs for Parkinson's Disease in Health‐Care Databases Using Machine Learning. Issue 12 (29th August 2022) - Courtois, Émeline; Nguyen, Thi Thu Ha; Fournier, Agnès; Carcaillon‐Bentata, Laure; Moutengou, Élodie; Escolano, Sylvie; Tubert‐Bitter, Pascale; Elbaz, Alexis; Thiébaut, Anne C.M.; Ahmed, Ismaïl
Abstract: Background: Available treatments for Parkinson's disease (PD) are only partially or transiently effective. Identifying existing molecules that may present a therapeutic or preventive benefit for PD (drug repositioning) is thus of utmost interest. Objective: We aimed at detecting potentially protective associations between marketed drugs and PD through a large‐scale automated screening strategy. Methods: We implemented a machine learning (ML) algorithm combining subsampling and lasso logistic regression in a case–control study nested in the French national health data system. Our study population comprised 40, 760 incident PD patients identified by a validated algorithm during 2016 to 2018 and 176, 395 controls of similar age, sex, and region of residence, all followed since 2006. Drug exposure was defined at the chemical subgroup level, then at the substance level of the Anatomical Therapeutic Chemical (ATC) classification considering the frequency of prescriptions over a 2‐year period starting 10 years before the index date to limit reverse causation bias. Sensitivity analyses were conducted using a more specific definition of PD status. Results: Six drug subgroups were detected by our algorithm among the 374 screened. Sulfonamide diuretics (ATC‐C03CA), in particular furosemide (C03CA01), showed the most robust signal. Other signals included adrenergics in combination with anticholinergics (R03AL) and insulins and analogues (A10AD). Conclusions: We identified several signals that deserve to be confirmed in large studies with appropriate consideration of the potential for reverse causation. Our results illustrate the value of ML‐based signal detection algorithms for identifying drugs inversely associated with PD risk in health‐care databases. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society